Гендерні аспекти трудових міграцій населення України - Герасименко, Г.В.; Позняк, О.В. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье исследуются гендерные особенности реализации трудовых миграций населением Украины. В этом контексте проанализированы мировые тенденции феминизации международной миграции, определены факторы, которые предопределяют актуальность и практическое значение внедрения гендерных подходов к миграционным исследованиям. Рассмотрена гендерная структура отечественных трудовых мигрантов, особенности организации и географии поездок, отличия в сфере занятости и условиях работы женщин и мужчин за границей. Очерчены специфические проблемы, с которыми сталкиваются украинские женщины на рынке труда иностранных государств, и предложены подходы к их решению. The publication is devoted to investigation of gender peculiarities of realization of labour migration of the population of Ukraine. In this context, the global trends of feminization of international migration are analyzed, the factors of urgency and practical importance of gender approaches to migration studies are defined. Gender structure of labour migrants is investigated, as well as peculiarities of organization and geography of trips, disparities in the area of employment and condition of work of women and men abroad. The specific problems, faced by the Ukrainian women at labour market of foreign countries are determined; the approaches to their solving are proposed.